Aplikasi E-Warga Berbasis Mobile Sebagai Media Komunikasi Warga Masyarakat - Dian Novian; Arip Mulyanto; Galang Leoni Yagri MS Punu; Indah Wardati (Universitas Negeri Gorontalo, 2021)
Communication between members of the community within the Neighborhood Association (RT) is often hampered due to the activities of each resident, making it difficult for the residents to share important information with each other. This study aims to build a mobile-based application as a communication medium for citizens in the RT environment. The research method used is the waterfall system development method which includes requirements analysis and definition, system and software design, implementation and unit testing, integration and system testing, and operation and maintenance. The results show that the mobile-based E-Warga Application can be used as a communication medium for citizens. The mobile-based E-Warga application helps the public to share important information, access various services and information needed.